Laparoscopic Transperitoneal Nephrectomy - Krivak, Lorette (Operating Room Nurses Association of Canada Journal, 1995)
This article will provide an overview of aLaparoscopic Transperitoneal Nephrectomy, including operational procedure and O.R. setup as performed at Concordia General Hospital in Winnipeg, Manitoba.